Convective Cooling Enhancement in Electronic Systems by Using Vibration - ABDALLA EBRAHEEM, AMMAR FAISAL (2018)
Electronics and heat have been linked due to the high demand. Every heat sink generates a specific temperature which yields to the generation of a thermal boundary layer profile that when disturbed; would allow for higher rates of heat dissipation. Inorder, to make this project feasible, a specific electronic device had to be selected and, in this case, it is a computer. Computers are the focus of this era since it can perform a higher level of data processing than a laptop. The selected computer model is Intel Xeon E5-2650 v3 2.3GHz which commonly used in the university. The heat sink’s (processor) area has been enlarged by the addition fins onto it, there is enough space inside the computer to allow for this. The purpose of the numerical simulation is to investigate the ideology of heat dissipation when the surface area is enlarged and since computers vibrate due to the cooling fan, that vibration is going to be induced to the enlarged heat sink as part of the simulation. Consequently, the enhancement that has occurred for both cases of the processor before and after the enlargement of the area are going to be compared and studied with the vibration induced at different amplitudes. Moreover, varying the amplitude of vibration to evaluate with would yield to enhanced heat dissipation is the main objective of this investigation. Finally, vibration has proved to enhance the heat transfer further than with only the surface area enlarged.